Analysis of heat-shock protein genes and their expression in Lactiplantibacillus plantarum SU-KC1a - CLARA MEIRINZHA PANG JULYANTO; ROBIN DOSAN; HANS VICTOR; MARCELIA SUGATA; TJIE JAN TAN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Julyanto CMP, Dosan R, Victor H, Sugata M, Tan TJ. 2024. Analysis of heat?shock protein genes and their expression in Lactiplantibacillus plantarum SU-KC1a. Biodiversitas 25: 2494-2499. Lactiplantibacillus plantarum is lactic acid bacteria commonly used as probiotics. Throughout the manufacturing and processing stages for incorporation into functional food products, probiotics encounter different stress conditions, including heat stress, which can affect their viability. In this study, the ability of L. plantarum SU-KC1a to withstand heat stress conditions was assessed by measuring cell viability after incubation at 37, 42, 47, and 52? for one hour. Additionally, the growth of SU-KC1a in liquid cultures under various high temperatures was monitored hourly for three hours. Total RNA was extracted from each culture, converted into cDNA, and amplified using hsp3 gene-specific primers. The results indicated a slower growth rate of SU-KC1a at higher temperatures, with 42? as the maximum temperature supporting growth. Visualization of hsp3 amplicon showed increased intensity following incubation at higher temperatures, indicating upregulation of hsp3 gene expression. To identify the presence of heat stress-related genes, whole genome sequence annotation data of SU-KC1a was compared to that of L. plantarum SK151, F75, and WCFS1. Lactiplantibacillus plantarum was found to possess two systems involved in protein repair in response to heat stress damage: chaperone and protease. In summary, L. plantarum SU-KC1a harbors heat shock protein genes, and their expression is upregulated following exposure to high temperatures.